Предмет: Алгебра,
автор: Anik227
Помогите пожалуйста,
Приложения:
Ответы
Автор ответа:
0
1. (а+3)(-а+3)=-(а+3)(а-3)=-(а²-9)
2.(-а-3)(а+3)=-(а+3)(а+3)=-(а+3)²
3.(-а-3)(а-3)-9=-(а+3)(а-3)-9=-(а²-9)-9=-а²+9-9=-а²
4.а²-(а-3)(3+а)=а²-(а-3)(а+3)=а²-(а²-9)=а²-а²+9=9
5.(а-3)(а+3)(а²+9)=(а²-9)(а²+9)=а^4-81
6.(a+3)(2a-5)-(a+3)(a-2)=(а+3)(2а-5-а+2)=(а+3)(а-3)=а²-9
2.(-а-3)(а+3)=-(а+3)(а+3)=-(а+3)²
3.(-а-3)(а-3)-9=-(а+3)(а-3)-9=-(а²-9)-9=-а²+9-9=-а²
4.а²-(а-3)(3+а)=а²-(а-3)(а+3)=а²-(а²-9)=а²-а²+9=9
5.(а-3)(а+3)(а²+9)=(а²-9)(а²+9)=а^4-81
6.(a+3)(2a-5)-(a+3)(a-2)=(а+3)(2а-5-а+2)=(а+3)(а-3)=а²-9
Похожие вопросы
Предмет: Английский язык,
автор: 1pipyka1
Предмет: Алгебра,
автор: anyapolka
Предмет: Алгебра,
автор: anyapolka
Предмет: Физика,
автор: zargarianangel
Предмет: Математика,
автор: Alisa199909